2010
DOI: 10.1073/pnas.1000675107
|View full text |Cite
|
Sign up to set email alerts
|

A domain swap approach reveals a role of the plant wall-associated kinase 1 (WAK1) as a receptor of oligogalacturonides

Abstract: Oligogalacturonides (OGs) released from the plant cell wall are active both as damage-associated molecular patterns (DAMPs) for the activation of the plant immune response and regulators of plant growth and development. Members of the Wall-Associated Kinase (WAK) family are candidate receptors of OGs, due to their ability to bind in vitro these oligosaccharides. Because lethality and redundancy have hampered the study of WAKs by reverse genetics, we have adopted a chimeric receptor approach to elucidate the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
540
2
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 636 publications
(575 citation statements)
references
References 47 publications
9
540
2
6
Order By: Relevance
“…8) and were significantly (FDR-corrected P = 0.006; Online Methods) enriched for genes involved in response to virus, suggesting that selection may indeed have contributed to maintaining some of the ancestral polymorphisms. We identified a total of four virus-response genes with haplotypes shared across all four species: CYCT1;4 (TAIR locus AT4G19600), which is involved in transcriptional activation of viral genes; GRIK1 (TAIR locus AT3G45240), which has a role in the metabolic regulation of virus-infected cells 26,27 ; NIG (TAIR locus AT4G13350), which is involved in nucleocytoplasmic trafficking of viral proteins 28 ; and WAK1 (TAIR locus AT1G21250), which activates an immunity response to damaged cell walls 29 .…”
mentioning
confidence: 99%
“…8) and were significantly (FDR-corrected P = 0.006; Online Methods) enriched for genes involved in response to virus, suggesting that selection may indeed have contributed to maintaining some of the ancestral polymorphisms. We identified a total of four virus-response genes with haplotypes shared across all four species: CYCT1;4 (TAIR locus AT4G19600), which is involved in transcriptional activation of viral genes; GRIK1 (TAIR locus AT3G45240), which has a role in the metabolic regulation of virus-infected cells 26,27 ; NIG (TAIR locus AT4G13350), which is involved in nucleocytoplasmic trafficking of viral proteins 28 ; and WAK1 (TAIR locus AT1G21250), which activates an immunity response to damaged cell walls 29 .…”
mentioning
confidence: 99%
“…Activation of defense responses by OGs increases resistance of Arabidopsis (Arabidopsis thaliana) and grape (Vitis vinifera) leaves against the necrotrophic fungus Botrytis cinerea (Aziz et al, 2004;Ferrari et al, 2007). Recently, the wallassociated kinase WAK1 has been identified as a receptor of OGs (Brutus et al, 2010;De Lorenzo et al, 2011).…”
mentioning
confidence: 99%
“…The elicitor activity of OGs depends on their length and degree of esterification (Osorio et al, 2008;Ferrari et al, 2013). It has been shown that pectic fragments can be perceived by WALL-ASSOCIATED KINASE1 (WAK1) and WAK2 (Kohorn et al, 2009;Brutus et al, 2010). Recognition of OGs activates downstream defense responses including reactive oxygen species production, ethylene production, and callose deposition (Ferrari et al, 2013).…”
mentioning
confidence: 99%